PERKEMBANGAN SEKOLAH ISLAM DI PONTIANAK PADA MASA KOLONIAL (1914-1941) - Mohammad Rikaz Prabowo; Dyah Kumalasari (Handep: Jurnal Sejarah dan Budaya, 2022)
This study aims to describe the state of education in Pontianak from 1914 to 1941. Many Islamic schools combined religious lessons with the colonial government’s curriculum during this period. This research fills the gap between previous studies that have not thoroughly discussed this educational contestation at the local level. The research used the historical method through the stages of heuristics, verification, interpretation, and historiography. This research shows that in the early 20th century, the colonial government established several schools, such as Europesche Lagere School (ELS) and Hollandsch Inlands School (HIS) in Pontianak. Dualism, discrimination, and gradualism had made these schools unreachable and unequal. The schools did not include religious lessons. It had an alledged impact on distance students from the original culture of the Indies population. This condition encouraged the change of the non-formal education model through a surau into a school to balance Dutch schools and the regulations of the Priesterraden and the Illegal Schools Ordinance. Ulama could no longer freely convey their teachings unless they had permission and recommendations. The first Islamic schools established in Pontianak were the Alqadriah (1914) and the Saigoniah (1925). The change in the form of the school was marked by the adoption of general subjects (Western knowledge) and the Dutch language. The established Islamic schools equated their curriculum with the levels and types of government schools. The Muhammadiyah school (1927) was of the volksschool type and was scouted by ‘Hizbul Wathan’. Al-Islamiyah College (1926) and Raudhatul Islamiyah College (1936) opened schakelschool, which the graduates equated with HIS.